Ansiedade, depressão e qualidade de vida em mulheres usuárias de contraceptivos hormonais orais - SOUZA, Flávia Cristina Barros de (2017)
Introduction: The use of combined oral contraceptives is common in women in their reproductive phase. Since its introduction in the 60's, symptoms of anxiety and depression have been cited as side effects and therefore with a reflection on the quality of life (QoL). Anxiety and depression are more common in women in their reproductive age. The association between anxiety, depression, QoL and hormonal contraceptives is still unclear, literature findings are still inconsistent. Objective: To identify symptoms related to depression, anxiety and quality of life in women using combined oral hormonal contraceptives at a Referral Hospital in São Luís - MA. Methodology: A cross-sectional study with a nonprobabilistic sample of 113 women attended at the gynecology outpatient clinic of Materno Infantil University Hospital in São Luís -MA. Depression was assessed by the BECK Inventory, the anxiety by the State-Trait IDATE and the QoL by the SF-36. For statistical analysis, the STATA 14.0 program was used (STATA Corporation, 2003). The categorical variables were presented by means of frequencies and percentages and the numerical by mean and standard deviation (mean ± SD) or median and interquartile range (P25-P75). To test the normality of numerical variables, the Shapiro-Wilk test was used. The Mann-Whitney test was used to compare the groups of the depression and anxiety variable and the Student's Independent T-Test to compare the groups of the variables of quality of life. The level of significance (p) was adopted with α of 0.05. Results: In the sample, the following means have prevailed: age 24.03 years (18 to 44), menarche 12.23 years (9 to 16), weight 58.9 kg (41 to 90 kg), BMI 22.66 (16, 79-36.05). Regarding behavioral habits, nonconsumption of alcohol and tobacco prevailed respectively with 73 (64.60%) and 111 (98.23%). In Groups A (use of COHC.) and B (without the use of COHC.) in relation to the type of anxiety and level of depression, there was no statistically significant difference between them. Asymptomatic women prevailed in relation to depression (Group A 32 / 82.05% and Group B 61 / 82.43%) and presence of anxiety/trait and anxiety/status in both groups. QoL was not impaired by the use of COHC, since in the eight domains the means were greater than 50%. Conclusion: The results show that, in this sample, there were no significant differences between the presence of anxiety, depression and altered quality of life in women who used or not combined oral hormonal contraceptives, therefore, their use does not cause states of anxiety or depressive. Thus the quality of life does not change.